2022
DOI: 10.1038/s41598-022-25652-x
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of cellulose nanocrystals based composites to build robust biomimetic scaffolds for bone tissue engineering

Abstract: Cellulose nanocrystals (CNC) are drawing increasing attention in the fields of biomedicine and healthcare owing to their durability, biocompatibility, biodegradability and excellent mechanical properties. Herein, we fabricated using fused deposition modelling technology 3D composite scaffolds from polylactic acid (PLA) and CNC extracted from Ficus thonningii. Scanning electron microscopy revealed that the printed scaffolds exhibit interconnected pores with an estimated average pore size of approximately 400 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…As a result, the film surface exhibited a tortuous structure, as observed in Figure d,e, which affects its mechanical properties. This finding aligns with the work of N’Gatta et al, where they demonstrated that an increase in CNC percentage of more than 3% leads to a poor hydrogen-bonding interaction of CNC with the poly­(vinyl alcohol) (PVA) within the matrix, resulting in the excessive agglomeration and leading to roughness in its cross-section …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, the film surface exhibited a tortuous structure, as observed in Figure d,e, which affects its mechanical properties. This finding aligns with the work of N’Gatta et al, where they demonstrated that an increase in CNC percentage of more than 3% leads to a poor hydrogen-bonding interaction of CNC with the poly­(vinyl alcohol) (PVA) within the matrix, resulting in the excessive agglomeration and leading to roughness in its cross-section …”
Section: Resultssupporting
confidence: 91%
“…This finding aligns with the work of N'Gatta et al, where they demonstrated that an increase in CNC percentage of more than 3% leads to a poor hydrogenbonding interaction of CNC with the poly(vinyl alcohol) (PVA) within the matrix, resulting in the excessive agglomeration and leading to roughness in its cross-section. 40 Incorporating 1 mL of AgNP2 into the 1F-25G-25S-50C composite film did not alter the surface or cross-section morphology (Figure 7f,f′). However, increasing the amount of AgNP2 solution to 2 and 3 mL resulted in a rough surface morphology (Figure 7g,h) as well as the cross-section (Figure 7g′,h′).…”
Section: Resultsmentioning
confidence: 92%
“…The result shows that the scaffold can promote mineralization faster than PLA only. Moreover, the cytocompatibility tests revealed that the scaffold is compatible with and non-toxic for bone cells [58].…”
Section: Bone Tissue Engineering Materialsmentioning
confidence: 98%
“…For instance, nanocrystals have been further developed by the utilisation of 3D printing to further develop the technology and derive increased utility. [99][100][101] Furthermore, the prospect of loading nanomaterials in nano-bers presents an additional opportunity for further manufacture. 102 These could be extrapolated to NCC for potential additive manufacturing.…”
Section: Additive Manufacturingmentioning
confidence: 99%